Fundamentos de la regulación del crowdfunding: a propósito del Decreto de Urgencia 013-2020 que establece el Régimen Jurídico del Financiamiento Participativo Financiero - Jiménez Alemán, José Alonzo (Pontificia Universidad Católica del Perú, 2021)
The financing market is one of the cornerstones for the promotion of entrepreneurship, innovation and job creation. In this regard, participatory financing (also known as crowdfunding) is positioned as an important credit tool that, among other characteristics, through technological innovation, creates a flexible ecosystem of direct intermediation that allows investors and promoters to connect on a massive scale. At the same time, it ensures an effective competition of financing sources in the credit market.In this article, the author presents a general framework on crowdfunding and critically analyzes its regulation in the Peruvian legal system. Along the same lines, taking into consideration comparative experience, he proposes some regulatory recommendations in order to promote the growth of crowdfunding and ensure its proper functioning in the market.

El mercado de financiamiento es uno de los ejes de la promoción del emprendimiento, innovación y la creación de empleo. En ese orden de ideas, el financiamiento participativo (o también denominado crowdfunding) se posiciona como una herramienta de crédito importante que, entre otras características, a través de la innovación tecnológica, crea un ecosistema flexible de intermediación directa que permite conectar de forma masiva a inversores y promotores. A su vez, asegura una competencia efectiva de fuentes de financiamiento en el mercado de créditos.En el presente artículo, el autor expone un marco general sobre el crowdfunding y analiza críticamente su regulación en el régimen jurídico peruano. En esa misma línea, tomando en consideración la experiencia comparada, propone algunas recomendaciones normativas, a fin de potenciar el crecimiento de la figura y garantizar su adecuado funcionamiento en el mercado.
The regulation of crowdfunding: regarding emergency Decree 013-2020 which establishes the legal regime for financial crowdfunding
Keywords: Crowdfunding; Superintendencia del mercado de valores; Financiamiento participativo financiero; Inversionistas; Sociedades administradoras; Promotores; https://purl.org/pe-repo/ocde/ford#5.05.01